Housing Estate with Flood Resilience : Merging Housing Features and Drainage Design - Darren Mah, Yau Seng; Tang, M.S.T.; Norazlina, Bateni; Tri Nugraha, Adi Kesuma; Frederik Josep, Putuhena (Semarak Ilmu Publishing, 2025)
This paper describes the human intervention to increase flood resilience in a housing estate. Stormwater storage facility is a structure designed to temporarily hold water, in which such a structure was tried for underneath the car porch and front road of a terrace house. A design rainfall of 5-minute, 10-year average recurrent interval intensity was selected for urban runoff analyses. A row of 12 terrace houses with a land area 2,472 m2 was selected as the study area. An intervention was formulated, in which it consisted of the car porches embedded with a series of underground water storage facilities having 46.9 m3 of effective storage volume and receiving water from 820 m2 of catchment area; combined with the front road embedded with a series of underground water storage facilities having 55.2 m3 of effective storage volume and receiving water from 278 m2 of catchment area. The characteristics of the intervention in the study area were represented through Storm Water Management Model version 5.0 to simulate the urban runoff in pre-development and post-development conditions, as well as the intended intervention. The results showed that the intervention had reduced 54% of peak flow compared with post-development condition. The intervention also achieved flow nearest to the pre-development condition. No overflowing was predicted in the drainage system.